Role of High-Resolution Computed Tomography in Classifying Pneumatization of the Temporal Bone: Typical Patterns, Prevalence, and Implications - RC Rohit; Assvath Oobula Chandru; Sathish S Babu; Kavya Priyadharshini Natarajan (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Introduction: Pneumatization patterns in the temporal bone have been implicated in the prognostic outcomes of various pathological conditions, such as cholesterol granulomas, otitis media, and cholesteatomas. This study investigated how high-resolution computed tomography (HRCT) helps to classify pneumatization patterns in the temporal bone, exploring its impact on the pathogenesis, surgical outcomes of temporal bone diseases, and its association with age and gender. Methods: HRCT of temporal bone of fifty patients of age 13 years and more with normal findings were included. The petrous apex, mastoid, and infra-labyrinthine regions’ pneumatization patterns were categorized using previously published grading methods. Results: The dominant pattern of pneumatization in the petrous apex was classified as group 2, indicating that less than 50% of the pneumatization was located medially in the labyrinth. Conversely, in the mastoid, the prevailing pattern was group 4, which signifies hyper-pneumatization. In the infra-labyrinthine region, the prevailing pattern was categorized as type B, indicating limited pneumatization. It was found that patients who exhibited augmented pneumatization in one compartment of the temporal bone tended to display similar changes on the opposite side and in other compartments on the same side (P < 0.05). Importantly, it was observed that younger age (P < 0.001) and male gender (P = 0.001) were associated with increased pneumatization in the petrous apex and infra-labyrinthine compartments. Conclusion: Different compartments of temporal bone show varying degrees of pneumatization. The level of pneumatization of the temporal bone is highly associated with age and sex.